Управление устойчивостью пород в зонах дизъюнктивных нарушений - Кольчик, Е.И.; Кольчик, И.Е.; Болбат, В.А. (Физико-технические проблемы горного производства, 2007)
Наведено результати аналітичних досліджень та спосіб підвищення стійкості зруйнованих порід у зонах диз’юнктивних порушень. The results of analytical researches and method of decision of stability of the rocks in the zone of disjunctive dislocations are resulted.